Effect of simulation-based teaching on nursing skill performance: a systematic review and meta-analysis - Asegid Agezegn; Assefa Nega (Sciendo, 2021)
To summarize and produce aggregated evidence on the effect of simulation-based teaching on skill performance in the nursing profession. Simulation is an active learning strategy involving the use of various resources to assimilate the real situation. It enables learners to improve their skills and knowledge in a coordinated environment.